Hemiacetalmeroterpenoids A–C and Astellolide Q with Antimicrobial Activity from the Marine-Derived Fungus Penicillium sp. N-5 - Tao Chen; Wencong Yang; Taobo Li; Yihao Yin; Yufeng Liu; Bo Wang; Zhigang She (Marine Drugs, 2022)
Four new compounds including three andrastin-type meroterpenoids hemiacetalmeroterpenoids A-C (1–3), and a drimane sesquiterpenoid astellolide Q (15), together with eleven known compounds (4–14) were isolated from the cultures of the marine-derived fungus Penicillium sp. N-5, while compound 14 was first isolated from a natural source. The structures of the new compounds were determined by analysis of detailed spectroscopic data, and the absolute configurations were further decided by a comparison of the experimental and calculated ECD spectra. Hemiacetalmeroterpenoid A (1) possesses a unique and highly congested 6,6,6,6,5,5-hexa-cyclic skeleton. Moreover, the absolute configuration of compound 14 was also reported for the first time. Compounds 1, 5 and 10 exhibited significant antimicrobial activities against Penicillium italicum and Colletrichum gloeosporioides with MIC values ranging from 1.56 to 6.25 μg/mL.